STRATEGIC MANAGEMENT PT PHAPROS TBK - Pusparani, I Gusti Ayu; Murhadi, Werner R. (International Journal of Social Service and Research, 2024)
The pharmaceutical industry is one of the most competitive industries in the world. This paper aims to discuss the shortcomings, weaknesses, threats, opportunities, and strategies that PT Phapros Tbk can implement to realize the company's vision. This research contributes to the field of strategic management by providing a comprehensive analysis of the pharmaceutical industry's internal and external environment using SWOT analysis. In addition, this paper provides a practical framework for understanding and addressing strategic challenges. The research results show that the pharmaceutical and herbal medicine industries have a strong and recognizable identity in both domestic and international markets. This study could include a focus on sustainable and innovative production techniques for herbal and medical device products.